The Broken Pitcher A Comedy in One Act - von Kleist, Heinrich (UNC Studies in the Germanic Languages and Literatures, 1961)
An imperishable gem of German literature, Kleist's "The Broken Pitcher" is pure comedy. The author's handling of the theme-the judge as culprit-shows supreme mastery. This translation by Bayard Q. Morgan, originally published in 1961, is faithful in form.